2010
DOI: 10.1007/s12185-010-0581-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cell versus bone marrow transplantation from HLA-identical sibling donors in patients with leukemia: a propensity score-based comparison from the Japan Society for Hematopoietic Stem Cell Transplantation registry

Abstract: We retrospectively analyzed the results of 707 adult patients who underwent myeloablative peripheral blood stem cell transplantation (PBSCT) (n = 365) and myeloablative bone marrow transplantation (BMT) (n = 342) for leukemia from HLA-identical sibling donors between 2000 and 2005 using the propensity score method. The results were obtained from the Japan Society for Hematopoietic Cell Transplantation registry. Multivariate Cox analysis showed that PBSCT was associated with lower overall survival (OS) in stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 37 publications
3
25
1
Order By: Relevance
“…These results are consistent with the results of randomized studies and registry studies comparing PBSCT with BMT. [16][17][18] We also found that PBSCT was associated with a higher risk of secondary solid cancer compared with BMT among adult patients with high-risk disease. Previous studies found that chronic GvHD was a major factor associated with risk of secondary solid cancer.…”
Section: Discussionmentioning
confidence: 55%
“…These results are consistent with the results of randomized studies and registry studies comparing PBSCT with BMT. [16][17][18] We also found that PBSCT was associated with a higher risk of secondary solid cancer compared with BMT among adult patients with high-risk disease. Previous studies found that chronic GvHD was a major factor associated with risk of secondary solid cancer.…”
Section: Discussionmentioning
confidence: 55%
“…Nagafuji et al retrospectively evaluated outcomes after HLA-matched sibling BMT and PBSCT in Japan using Japanese national registry data. [13] In this study, the incidence of grades III–IV acute GVHD was 14% and 5% in the HLA-matched sibling PBSCT and BMT, respectively, with a hazards ratio of 2.23 (95% CI, 1.04–4.78). These reports suggest that the incidence of severe acute GVHD was very low after HLA-matched sibling BMT in the Japanese population and the risk ratio of severe acute GVHD in PBSCT vs. BMT was much larger in Japanese than in Caucasian and other populations (2.23 vs. 1.39).…”
Section: Introductionmentioning
confidence: 63%
“…It is less likely that the particular characteristics of chronic GVHD in patients with ATL biased the results, because the incidence rate and median onset day of chronic GVHD in our cohort were similar to those reported in previous studies evaluating the incidence of chronic GVHD among Japanese patients, most of whom had received allogeneic HCT for myeloid neoplasms or acute lymphoblastic leukemia. [30][31][32] Conceivably, the rapid tempo of disease recurrence of ATL might be such that chronic GVHD is less potent in terms of harnessing clinically relevant graft-versusleukemia responses compared with acute GVHD. However, the results of our analysis regarding the effect of chronic GVHD should be interpreted with caution because the number of patients evaluable for chronic GVHD was relatively small in our study for providing sufficient statistical power.…”
mentioning
confidence: 99%